(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This paper examines the evolution of the institution of compensation for harm caused to consumers of medical services in the Republic of Uzbekistan. It identifies the main stages in the formation and development of this institution: from the constitutional recognition of the right to health protection and judicial protection to the emergence of a modern intersectoral model integrating the norms of civil, medical, consumer, and procedural law. Particular attention is paid to the provisions of the Civil Code of the Republic of Uzbekistan, the Laws “On the Protection of Citizens’ Health”, “On Consumer Protection”, and “On Mediation”, as well as to procedural mechanisms for protecting patients’ rights. The paper substantiates that, in contemporary Uzbek law, a patient acts not only as a recipient of medical care but also as a consumer of medical services who is entitled to demand quality, safety, proper information, and compensation for pecuniary and non-pecuniary harm. It concludes that the institution of compensation for harm caused to consumers of medical services has acquired a complex intersectoral character and is developing towards a stronger patient-centred approach, broader guarantees of judicial and extrajudicial protection, and improved compensation mechanisms. The paper may be useful both for professional participants in the healthcare sector and for researchers engaged in the legal protection of patients.